Water quality of the Atibaia river in the city of Paulínia/SP: evaluation of the Electrical Conductivity and Chloride variables - Montovani, Camila Pereira; Coneglian, Cassiana Maria Reganhan; Poletti, Elaine Cristina Catapani (Ciência e Natura, 2021)
The present study aimed to evaluate the characteristics that most influenced the water quality variability of the Atibaia river in the city of Paulínia/SP, the coordinates of the water collection point are given by 22º44’23”(S) and 47º07 ’ 40 ”(W), in the dry and rainy seasons, from 2006 to 2016. The data used in this study come from the monitoring of parameters carried out in the spring by a research team, accompanied by periodic collections of surface water samples and analyzes laboratory tests. The parameters addressed included: precipitation, temperature, Hydrogenionic potential (pH), turbidity, thermotolerant coliforms (Escherichia coli (E. coli)), dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total nitrogen (Ntotal), total phosphorus (Ptotal), total dissolved solids (TDS), electrical conductivity (EC) and chlorides (Cl-). Water quality was assessed using linear correlation analysis, using the Pearson Correlation coefficient (r), and Multivariate Analysis, using Principal Component Analysis (PCA). The presence of EC, Cl- and COD in both periods indicates quality characteristics related to the mineralization of organic compounds present in the water and the eutrophication process.